"THERE IS A PLACE WHERE TERROR IS GOOD": aeschylus' oresteian myth of law and lacan's theory of the four discourses. Issue 5 (3rd September 2018) - Kelly, Sean J.
Abstract: This article performs an analysis of Aeschylus' tragedy the Oresteia within the Lacanian model of the Four Discourses. The author contends that the myth, which dramatizes the transition from the ancient conception of the law based on familial revenge to the modern institution of law, may be viewed as a shift from a failed Master's Discourse to the University Discourse. The cycle of revenge killings performed throughout the tragedy, culminating in Orestes' murder of his mother, may be considered signifying acts of self-sovereignty in the name of Dikê, or justice. However, the traumatic "product" of these acts – the murder that signifies the enactment of the law of revenge – parallels the product of the Master's Discourse, the objet a, or traumatic kernel of the real. Ultimately, with the implementation of Athena's new legal order based on alienating institutionalized knowledge and practices, this traumatic product is rearticulated in the formation of the superego and in relation to the Sovereign Good.